FAKTOR YANG MEMPENGARUHI PURCHASE INTENTION PRODUK KECANTIKAN BERLABEL GREEN PRODUCT DIMEDIASI ATTITUDE - Lily Purwianti; Dame Afrina Sihombing; Liana Ester (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2023)
The beauty industry is growing over time, giving rise to new problems, namely the accumulation of rubbish and cosmetic waste, therefore companies need to implement green marketing in the process. Generation Z really likes brands that always prioritize and implement green marketing. In this research, we examine the factors that influence Purchase Intention towards beauty products, especially green products in the city of Batam. The method used in this research is a quantitative method. Information data was obtained using a distributed survey method using data from 385 respondents who live in the city of Batam and were born in 1997-2012 or generation Z, sampling using a purposive sampling method. The tool used to manage data is Smart PLS. The research results prove: Attitude has a significant influence on Purchase Intention, Health Consciousness has no influence on Attitude, Perceived Behavioral Control has a significant influence on attitude, Price has a significant influence on Attitude and Subjective Norm has a significant influence on Attitude. Another finding is that Attitude mediates the influence of Environmental Concern, Perceived Behavioral Control, Subjective Norm on Purchase Intention, while Attitude does not mediate the influence of Health Consciousness on Purchase Intention. Keywords: Attitude, Generation Z, Purchase Intention